Nature of Penicillin-Induced Growth Inhibition of Mycoplasma neurolyticum - Wright, D. N. (1967)
When penicillin was added to cultures of Mycoplasma neurolyticum in amounts up to 1,000 units per ml, lag time and generation time were increased and the total population was reduced in proportion to the antibiotic concentration. Although growth suppression by penicillin was complete, the death rate was slow and linear over periods up to 12 days. Growth after induced lag was due to a decay in penicillin activity and was not the result of mutant selection. However, repeated transfer in media which contained increasing concentrations of penicillin resulted in normal growth of M. neurolyticum at penicillin levels as high as 1,000 units per ml. Penicillinase did not play a role in recovery from penicillin-induced lag, and the inactive penicillin molecule did not prevent normal growth of M. neurolyticum. Removal of penicillin from the medium by washing or penicillinase during the induced lag was immediately followed by normal growth of the organism. These results suggest a reversible antibiotic function for penicillin which prevents multiplication of the organism by means unrelated to cell wall formation.